Sejarah Makassar dan Tradisi Literasi - Ilham Daeng Makkelo (Lembaran Sejarah, 2019)
This article analyses two main topics; the history of the origin and development of the kingdom of Makassar in south Sulawesi and the historiography of the South Sulawesi area and its literary tradition. This area is one of the regions in Indonesia that has a literary tradition which developed since the appearance of the lontaraq script as a medium for the record keeping of political and social life of the community. Various literary classics have been produced from this tradition, such as the La Galigo epic, various state and social regulations, genealogy tracts and personal journals. The history and culture of south Sulawesi has become of particular interests for researchers in Indonesia and abroad. The central focus of its historiography has been the glory days of the kingdom of Makassar in the 16-17 th century. The centuries after the fall was a period of minimal production of literary and historical works. Its literary tradition made a resurgence in the post-colonial period but had sputtered out by the end of the 1960s. During the New Order period, the regime’s strong control has reduced the space for literary expression and resulted in stagnating literary production. Since the Reformasi period, efforts to rejuvenate the literary tradition of south Sulawesi has appeared.